EPIDEMIOLOGY AND HEALTH: DESCRIPTIVE ANALYSIS OF THE LIFESTYLE AND (EV) LEVELS OF HABITUAL (NAFH) PHYSICAL ACTIVITY OF ACADEMICS OF PHYSICAL EDUCATION, CE, BRASIL (Fiep Bulletin - online, 2014)
Introduction:A inactivity is one of the risk factors that contribute to the presence of individuals' chronic-degenerative diseases. The lifestyle and their habits in the daily determine favorable conditions of health and life quality. The Objective of this study is to analyze the lifestyle and (EV) the level of academics' of Physical education habitual (NAFH) physical activity. The methodology elapses of a study of field, traverse, with data primary, quantitative and of descriptive character, with sample stratified probabilística of 42 individuals, with average of age of academics' of the course of Physical education of the University 29,4+5,5 years it is Worth of Acaraú (GRAPE), submitted to the translated of Russel R. questionnaires of habitual physical activity Pâté and of the Profile of the Lifestyle mentioned in Nahas (2001). The analytical plan used program SPSS 13.0 for average statistics, minimum, maximum and percentile, test of sig of Friedman, correlation r of Pearson. The Results found averages of 27,59 pts for EV, and 2,4% were classified of very bad, 16,7% of regulating, 61,9% acceptable, 16,7% good and 2,4% very good; preventive (5,52+2,31pts) behavior, relationship (7,16+1,80 pts) and stress (5,26+2,02 pts) control, physical (4,78+2,29 pts) activity and nutrition (4,85+1,80 pts) and as for the levels of NAFH the average was of 11,97 pts classifying them of moderately assets, and 64,3% activate, 33,3% moderately assets (MILL) and 2,4% inactive; he/she was not correlations above r=0 ,611, considered of drop for moderate, for the variables analyzed in EV and NAFH and there were significant differences among the scores of the same of p=0 ,000. Conclusions: EV is considered acceptable and classified NAFH of it MILLS, and the domains of physical activity and nutrition are what more needs change, and there are no associations among the lifestyle habits adopted and physical activity.
Keywords: Lifestyle; Habitual Physical Activity; Physical education